Eksplorasi dan deskripsi keanekaragaman morfologi aksesi ubi jalar (Ipomoea batatas L.) di Distrik Nabire dan Nabire Barat Kabupaten Nabire - Yanti Wasti, Tris; Mawikere, Nouke Lenda; Prabawardani, Saraswati; Abbas, Barahima; Wibawati, Zarima; Dare, Darius; Moeljono, Soetjipto (Cassowary, 2025)
The purpose of this study was to explore and describe the morphological diversity of sweet potato accessions in Nabire and West Nabire Districts, Nabire Regency. The study was conducted in several villages in Nabire and West Nabire Districts, with altitudes ranging from 3 to 10 m above sea level. The study lasted for 2 months, from December 2024 to January 2025. The study was conducted using a descriptive method with direct observation techniques in the field. The determination of the research location was intentional (purposive sampling), by selecting areas where farmers cultivate sweet potatoes. Observations of plant morphological characters were carried out by the description guide by Huaman (1997). Observations on sweet potato accessions included morphological characters of stems or tendrils, leaves, and tubers. The results of the observations were analyzed, tabulated, and presented in tables and figures. The results of exploration in Nabire District (Sanoba, Kalimangga, Kalibobo, Wonorejo Village) and West Nabire District (Bumiraya, BR-Menou, Kalimerah, Gerbangsadu Village) obtained 70 sweet potato accessions. The number of sweet potato accessions cultivated in Nabire District is more (37 accessions) compared to West Nabire District (33 accessions). From the results of the study, a description of the morphology of the stems, leaves, and tubers of sweet potato plants in Nabire and West Nabire Districts was obtained with a fairly high level of diversity, such as: Stem (tendrils) character from non-twisting to twining, upright type to very creeping type, dominant tendril color from green to dark purple, and from hairless to thickly hairy. Leaf characteristics range from heart-shaped to almost separate, serrated leaf curve type to deep (finger-like), the number of leaf curves varies from 1,3,5,7,9, and the color of the leaves ranges from greenish yellow to purple on both the upper and lower leaves. The tuber characteristics range from round to irregular/curved length, and the dominant color of the tuber skin ranges from white to dark purple.